The safety benefits of older drivers attending an in-person licence renewal. (June 2020) - Koppel, Sjaan; Bugeja, Lyndal; Stephens, Amanda; Cartwright, Anna; Osborne, Rachel; Williams, Gabrielle; Peiris, Sujanie; Di Stefano, Marilyn; Charlton, Judith L.
Abstract: Introduction: This study systematically reviewed the literature on key issues relating to the safety benefits of older drivers attending an in-person licence renewal. This included identifying: 1) screening tools that are suitable for inclusion in a populationbased in-person licence renewal process for drivers aged 75 years and older which: a) can be administered by non-health professionals (or via a computer terminal/smart device), and b) are compatible with Australian fitness to drive requirements; 2) the evidence that in-person licence renewal policies are associated with safety benefits, as defined by: a) a reduction in motor vehicle crash risk, or b) on-road driving test outcomes. Methods: This review was registered with PROSPERO 2019: CRD42019120809. A systematic search of public health, psychology and transport databases was conducted on March 20th 2019. Results: Five studies published between 1986 and 2011 met the inclusion criteria. The review did not identify any suitable screening tools for inclusion in a population-based in-person licence renewal process for older drivers. There was inconclusive evidence regarding the safety benefits associated with in-person licence renewal policies for older drivers. Two studies reported that these policies were associated with a reduced crash risk. However, two studies reported that these policies were not associated with a reduced crash risk, and a third study provided inconclusive evidence. It is important to note that the included studies were conducted across different licensing jurisdictions, with different in-person licence renewal policies – both with and without vision and cognitive testing, which limit the generalisability of the findings. Conclusions: It is recommended that a population-based controlled research study in multiple licensing jurisdictions is conducted to specifically investigate the safety benefits of in-person licence renewal policies, as well as the efficacy of different components (including screening by health professionals prior to renewal), as a means to reduce road trauma. Highlights: Literature on safety benefits of older drivers attending an in-person licence renewal was systematically reviewed. Five studies published between 1986 and 2011 met the inclusion criteria. Review did not identify any suitable screening tools for inclusion in a population-based in-person licence renewal process. Inconclusive evidence regarding the safety benefits associated with in-person licence renewal policies. Population-based controlled research study is needed to investigate the efficacy of in-person licence renewal polices.